Entrepreneurship in Former Yugoslavia Diversity, Institutional Constraints and Prospects (Springer International Publishing, 2018)
This volume offers a comprehensive state-of-the-art portrait of entrepreneurship and small business management issues in former Yugoslavian countries. Further, it provides a wealth of theoretical and empirical evidence on the role of entrepreneurship in transition economies and emerging markets. Country-based studies identify the processes in each country that attract financial investors and yield new business and employment opportunities. In addition, the studies highlight institutional constraints and political factors that hinder the development of entrepreneurship in these countries, and offer recommendations for policymakers on how to improve the general business environment. This book will appeal to entrepreneurship researchers, as well as public policymakers in transition economies and emerging markets. .